2019
DOI: 10.3390/insects11010006
|View full text |Cite
|
Sign up to set email alerts
|

“Generalist” Aphid Parasitoids Behave as Specialists at the Agroecosystem Scale

Abstract: The degree of trophic specialization of interacting organisms impacts on the structure of ecological networks and has consequences for the regulation of crop pests. However, it remains difficult to assess in the case of parasitoids. Host ranges are often established by listing host records from various years and geographic areas in the literature. Here, we compared the actual hosts exploited at a local farm-scale by aphid parasitoids (Hymenoptera: Aphidiinae), to the available species listed as hosts for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 74 publications
3
9
0
Order By: Relevance
“…Mummification percentages on M. persicae were almost four times higher in cultivated plants than in plants growing in the borders, even though its abundance was similar in both plant types. Similar differences in mummification percentages were observed in French cereal agroecosystems, where proximity to naturally vegetated borders did not contribute to an increase in aphid parasitism (Damien et al., 2017); likewise, a comparison between crops of Brassicaceae, maize and wheat, and the uncultivated habitats surrounding the fields showed similar findings (Derocles et al., 2020). In Argentina, similar results were obtained in horticultural fields and their borders, with mummification percentages of M. persicae being four times higher in cultivated than in spontaneously growing plants (Jaureguiberry et al., 2010).…”
Section: Discussionsupporting
confidence: 55%
“…Mummification percentages on M. persicae were almost four times higher in cultivated plants than in plants growing in the borders, even though its abundance was similar in both plant types. Similar differences in mummification percentages were observed in French cereal agroecosystems, where proximity to naturally vegetated borders did not contribute to an increase in aphid parasitism (Damien et al., 2017); likewise, a comparison between crops of Brassicaceae, maize and wheat, and the uncultivated habitats surrounding the fields showed similar findings (Derocles et al., 2020). In Argentina, similar results were obtained in horticultural fields and their borders, with mummification percentages of M. persicae being four times higher in cultivated than in spontaneously growing plants (Jaureguiberry et al., 2010).…”
Section: Discussionsupporting
confidence: 55%
“…Contrary to several other Aphidiinae parasitoids, using molecular markers, A . ervi was proposed to be a ‘true’ generalist at the scale of an agroecosystem [ 15 ]. As no differentiation was observed according to the host plant, we can then expect natural habitats and other crops like Fabaceae crops to be reservoirs of A .…”
Section: Discussionmentioning
confidence: 99%
“…Even though no host-associated genetic differentiation has been observed here, it has been shown that A . ervi does not equally use its potential host range [ 15 , 57 , 60 ]. This is due to host fidelity through imprinting [ 57 , 60 ] or genetic factors [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2010) (but see Derocles et al . 2020). A feature of our findings was implicit host specificity among the native New Zealand parasitoids; each endemic aphid species was successfully parasitised by a distinct Aphidiinae lineage, with geographically separated Aphidiinae populations having the same or very closely related COI haplotype.…”
Section: Discussionmentioning
confidence: 99%